Pengetahuan Dan Ketrampilan Kader Tentang Penggunaan Alat Antropometri Dalam Deteksi Dini Balita Stunting - Dwi Ertiana; Taurisiawati, Dewi; Prasetya Ningsih, Susan; Taukhid, Muhammad (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Posyandu cadres play a crucial role in the early detection of stunting among toddlers through anthropometric measurements; therefore, they are required to possess adequate knowledge and skills. This study aimed to describe cadres’ knowledge and skills in using anthropometric tools in Purwokerto Village, Kediri Regency. This descriptive quantitative research involved knowledge and skill variables. The study was conducted on July 8–10, 2025, with a population of 80 posyandu cadres and a sample of 67 active cadres selected through proportional random sampling. Research instruments included a knowledge questionnaire and a skill observation sheet covering aspects of concepts, functions, procedures, result interpretation, measurement practices, recording, and compliance with SOPs. Ethical approval was obtained prior to data collection. The results showed that 64% of the cadres had good knowledge, 27% had moderate knowledge, and 9% had poor knowledge. Regarding skills, 65–75% of the cadres were proficient in using various anthropometric tools (stadiometer, infantometer, digital scales, baby scales), 21–31% were moderately skilled, and 4–12% were less skilled. Further analysis indicated that cadres with good competence were mostly within the productive age group (36–45 years), had secondary education (SMA/SMK), and had more than five years of experience. However, weaknesses were still observed in recording and interpreting measurement results. In conclusion, most cadres demonstrated good competence, yet the shortcomings in recording and result interpretation indicate the need for practice-based training and regular evaluations to improve the accuracy of anthropometric measurements in accelerating stunting reduction efforts.